Monitoring The Utilization of Hotspots at Universitas Bina Darma as Facilities for Lecturers and Staff - Andri Rio Saputra (Jurnal Jaringan Komputer dan Keamanan, 2025)
Information and communication technology plays a crucial role in the educational sector, with the internet functioning as the primary medium for accessing academic resources. Universitas Bina Darma provides hotspot facilities for lecturers and staff to support operational activities such as file sharing, internet access, and campus promotion. Monitoring and analysis of hotspot usage during academic breaks are necessary to understand utilization patterns and ensure the effectiveness of the facility. This study aims to evaluate hotspot utilization by lecturers and staff by identifying the most frequently accessed websites and services. A case study approach was employed, incorporating tools such as Wireshark, Network Miner, and Advanced IP Scanner to monitor network activity. The findings indicate that academic breaks are predominantly used for campus promotion and work-related communication via social media. The proportion of social media usage relative to total Wi-Fi activity was 49% on Day 1, 51% on Day 2, 50% on Day 3, 61% on Day 4, 40% on Day 5, 52% on Day 6, and 45% on Day 7.